Egg albumin-folic acid nanocomplexes: Performance as a functional ingredient and biological activity - Arzeni, Carolina (2015)
The ability of egg white (EW) nanoparticles to bind folic acid (FA) and protect it through the gastrointestinal tract and the resulting properties of the mixtures as functional ingredient was investigated. Two kinds of EW nanoparticles (USN and TSN) were mixed with FA to generate nanocarriers (USF and TSF). The particle size distribution of USN remained unaltered after the binding of FA, while a little increase in particle size was observed for TSN. Zeta (ζ) potential and fluorescence intensity did not show any significant change after FA addition for both nanoparticles. The percentage of bound folic acid (% BFA) was 78.0 ± 9.1 and 79.7 ± 9.0, for USF and TSF, respectively. A slight formation of aggregates in the samples was observed after freeze-drying and redispersion of the nanocarriers, which was also confirmed by confocal laser scanning microscopy. Nanocarriers particle size did not change after adjusting the pH from 3 to 4, but strongly increased after adjusting it to 5, 6 or 7. The % BFA at pH 4 was similar to that at pH 3, but greatly decreased at pH 7. The bioavailability of FA for Lactobacillus rhamnosus was enhanced when the vitamin was incorporated in the form of digested nanocomplexes USF or TSF. The interaction of EW nanoparticles with FA has proven to be beneficial for the transport and release of FA after in vitro digestion.